A short review on the synthesis and advance applications of polyaniline hydrogels - Mir, Aleena; Kumar, Amit; Riaz, Ufana (RSC advances, 2022)
Conductive polymeric hydrogels (CPHs) exhibit remarkable properties such as high toughness, self-recoverability, electrical conductivity, transparency, freezing resistance, stimulus responsiveness, stretch ability, self-healing, and strain sensitivity. Due to their exceptional physicochemical and physio-mechanical properties, among the widely studied CPHs, polyaniline (PANI) has been the subject of immense interest due to its stability, tunable electrical conductivity, low cost, and good biocompatibility. The current state of research on PANI hydrogel is discussed in this short review, along with the properties, preparation methods, and common characterization techniques as well as their applications in a variety of fields such as sensor and actuator manufacturing, biomedicine, and soft electronics. Furthermore, the future development and applications of PANI hydrogels are also mentioned. Conductive polymeric hydrogels (CPHs) exhibit remarkable properties for advance technological applications.